"How to stop choking to death": Rethinking lesbian separatism as a vibrant political theory and feminist practice. Issue 2 (2nd April 2016) - Enszer, Julie R.
ABSTRACT: In contemporary feminist discourses, lesbian separatism is often mocked. Whether blamed as a central reason for feminism's alleged failure or seen as an unrealistic, utopian vision, lesbian separatism is a maligned social and cultural formation. This article traces the intellectual roots of lesbian feminism from the early 1970s in The Furies and Radicalesbians through the work of Julia Penelope and Sarah Lucia Hoagland in the 1980s and 1990s, then considers four feminist and lesbian organizations that offer innovative engagements with lesbian separatism. Olivia Records operated as a separatist enterprise, producing and distributing womyn's music during the 1970s and 1980s. Two book distributors, Women in Distribution, which operated in the 1970s, and Diaspora Distribution, which operated in the 1980s, offer another approach to lesbian separatism as a form of economic and entrepreneurial engagement. Finally, Sinister Wisdom, a lesbian-feminist literary and arts journal, enacts a number of different forms of lesbian separatism during its forty-year history. These four examples demonstrate economic and cultural investments of lesbian separatism and situate its investments in larger visionary feminist projects. More than a rigid ideology, lesbian separatism operates as a feminist process, a method for living in the world.